Can Social Responsible Investment and Gold be a Good Diversifier for Indonesia Sharia Investors? - Agustin, Isnaini Nuzula (Jurnal Keuangan dan Perbankan, 2022)
The COVID-19 Pandemic persists after the global financial crisis resumption of financial turbulence. This vulnerabilities phenomenon compelled investors to restructure their portfolio by implementing a well-diversification strategy. The Sharia Investment and Environment Social Governance (ESG) Investment are two types of investment that enormously attract investors' interest, partly due to their resilience in times of crisis. This study examines the market integration between Sharia stocks, ESG stocks, and Gold and empirically compares its integration in the period before and during the covid-19 Pandemic. The data used were daily closing prices on two Indonesia Sharia indices, ESG index and Gold price from January 2, 2015, to August 31, 2021. Through Johansen Cointegration, the results ascertain the cointegration among variables, implying limited diversification opportunities among assets in the long run. Vector Error Correction Model found the significant short-term relationship between the Sharia stock index and ESG investment in the pre-pandemic period but turned out to be insignificant during the Pandemic. Further, the finding confirms the Gold's ability as a good diversifier for both assets in the pre-pandemic period. However, during the Pandemic, it suggests that gold can indeed provide diversification gains only for the ESG index. Our results have imperative implications about the asset allocation under portfolio optimization.